Dynamics of Open Systems in Early Childhood Education: An Analysis of Organizational Adaptability in Integrating Policy Interdependence and Management Practices - Jaya Roza Azzukhrufi; Erny Roesminingsih; Nuphanudin Nuphanudin; Fitriana Fitriana (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2026)
Rapid policy transformations pose significant challenges for Early Childhood Education (ECE) institutions, frequently resulting in an analytical fragmentation between external mandates and internal management practices. Grounded in Open Systems Theory, this study examines how policy interdependence is systematically integrated as an emergent institutional outcome through organizational adaptability. Employing a qualitative case study design, data were collected from selected Indonesian ECE institutions via in-depth interviews, observations, and document analysis, and evaluated using the interactive analysis model. Findings reveal that ECE institutions navigate policy interdependence not through rigid compliance, but by actively habituating external mandates into daily collaborative routines. Pedagogical friction is resolved through peer-mediated adaptability and distributed pedagogical governance rather than top-down sanctions. Furthermore, the study identifies the Paradox of Regulated Flexibility, highlighting a critical gap between superficial bureaucratic compliance and authentic pedagogical internalisation. This research contributes to educational management theory by reconceptualising policy integration as an organizationally produced competence, asserting that government mandates succeed only when transformed into deeply embedded cultural habits within the ECE ecosystem.